Family-Centered Care Improves Clinical Outcomes of Very-Low-Birth-Weight Infants: A Quasi-Experimental Study - Lv, Bo; Gao, Xi-ronga; Sun, Jing; Li, Tao-tao; Liu, Zhen-ye; Zhu, Li-hui; Latour, Jos M. (Frontiers in Pediatrics, 2019)
Background: Survival of very-low-birth-weight infants is improving in neonatology and family-centered-care might contribute to premature infants’ clinical outcomes. Aim: To evaluate a family-centered care intervention on clinical outcomes of very-low-birth-weight infants. Methods: A quasi-experimental study was conducted in a Chinese NICU between June 2016 and June 2017. The intervention included parental education of basic care knowledge and skills followed by active participation in care for at least four hours a day. A total of 319 very-low-birth-weight infants were recruited by convenience sampling; intervention group n=156 and control group n=163. Primary outcome measures were weight at discharge, length-of-stay, breastfeeding, nasal feeding, total parental nutrition, re-admission, hospital expenses. Secondary outcome measures were infant complications. Results: Infants’ weight at discharge was higher in the interventions group (2654g vs 2325g, p<0.001). Nutritional outcomes improved significantly: breastfeeding rate 139 vs 91, p<0.001; days of total parental nutrition 25d vs 32d, p<0.001; gastric feeding days 23d vs 35d, p<0.001. Length-of-stay and hospital expenses did not differ between both groups. Improved infants’ complications were bronchopulmonary dysplasia (32 vs 51, p=0.031), retinopathy of prematurity (between groups no/mild and moderate/severe, p=0.003), necrotizing enterocolitis (6 vs 18, p=0.019), and re-admission rate (21 vs 38, p=0.023). No differences were observed in intraventricular hemorrhage and nosocomial infections. Conclusion: Very-low-birth-weight premature infants might experience improved clinical health outcomes when parents are present and caring from them. Family-centered care is as a beneficial care model for premature infants and should be recognized and implemented by NICUs where parents have currently limited access.